The role of Cdc42, ADF/cofilin, myosin II and waves during the establishment of neuronal polarity - Flynn, Kevin Carl, author; Bamburg, James R., advisor (Colorado State University. Libraries, 2008)
The establishment of neuronal polarity is an essential developmental process, underlying the unidirectional flow of information in neurons and the overall function of the nervous system. In cultured hippocampal neurons, the first signs of polarity occur as one of several undifferentiated processes begins to elongate rapidly to form the axon (axonogenesis). The regulation of the cytoskeleton and intracellular trafficking are crucial to the proper development of neuronal polarity. This dissertation explores both of these polarity-developing mechanisms, identifying actin-regulating components in the signaling pathways as well as characterizing growth-cone like "waves" that correlate with axonogenesis. This study begins by analyzing the functional consequences of the loss of the Rho GTPase, cdc42, on the polarization of hippocampal neurons. Neurons from the cdc42 knock-out (cdc42KO) mouse have severe deficiencies in their ability to extend axons in vivo and in culture which is exerted through the regulation of actin dynamics. The actin regulating protein, cofilin is normally asymmetrically enriched in its active form in axonal growth cones but in cdc42 KO neurons there is an increase in the phosphorylation (inactivation) of cofilin. Cofilin expression promotes axon growth, whereas cofilin knockdown results in polarity defects analogous to those seen upon cdc42 ablation. Taken together, these data suggest that cdc42 is a key regulator of axon specification and that cofilin is a downstream effector of during this process. Though these studies suggest the involvement of cofilin downstream of cdc42; active cofilin cannot rescue polarity deficits in cdc42KO neurons. This suggests that other actin regulating proteins may also be required for axon formation. The actin motor protein, myosin-II also shows an increased activation in the cdc42KO brain. Inhibition of myosin II activity promotes axon formation and acts in synergy with cofilin on inducing supernumerary axons. Furthermore, the combined inhibition of myosin and activation of cofilin rescues axon formation in cdc42KO neurons while either treatment individually does not. Thus, the concurrent inhibition of myosin and activation of cofilin can contribute to the regulation of actin dynamics during axon specification. Axon specification is dependent on the transport of materials to the developing axonal growth cone. "Waves"-growth cone-like structures, propagate down neurites and correlate with neurite extension; thus, waves have been suggested as a mechanism for transporting materials that support this growth. Waves occur in all processes during early neuronal development, but are more frequent in the developing axon. Proteins enriched in axonal growth cones are also localized to waves and proteins such as cofilin and actin appears to be transported via waves to the growth cone, suggesting that waves represent a transport mechanism. Wave arrival at neurite tips was also coincident with an increase in growth cone size and dynamics. In addition, waves can promote neurite branching, either by supporting the growth of existing branches or by facilitating the growth of nascent branches. Waves are observed in neurons in organotypic hippocampal slices, a 3-dimensional growth environment reflecting the in vivo environment. Together, these data indicate that waves contribute to axon differentiation and growth both through the transport of actin and by increasing growth cone dynamics.
Zip file contains 19 AVI files.
Keywords: actin; cdc42; cofilin; myosin II; neuronal polarity; molecular biology; neurosciences; cellular biology